2008
DOI: 10.1111/j.1365-2265.2008.03319.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnicity on IGF‐I and procollagen III peptide (P‐III‐P) in elite athletes and its effect on the ability to detect GH abuse

Abstract: The GH-2000 detection method based on IGF-I and P-III-P would be valid in all ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…P3NP levels rise after a bone fracture or soft tissue muscle injury (9,(33)(34)(35). P3NP response to rhGH administration may be affected by the age, gender, and stage of pubertal maturation, whereas ethnicity has only a small effect (6,17,36). Our data show that P3NP also increased after testosterone administration in men who did not receive rhGH; thus, the P3NP response is not unique to rhGH.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…P3NP levels rise after a bone fracture or soft tissue muscle injury (9,(33)(34)(35). P3NP response to rhGH administration may be affected by the age, gender, and stage of pubertal maturation, whereas ethnicity has only a small effect (6,17,36). Our data show that P3NP also increased after testosterone administration in men who did not receive rhGH; thus, the P3NP response is not unique to rhGH.…”
Section: Discussionsupporting
confidence: 49%
“…P3NP has been explored as a marker of GH doping in athletes (6,10,12,13,15,17) and shown to respond to exercise (11) and testosterone (10). In previous studies, administration of supraphysiological doses of rhGH has been associated with significant elevations of P3NP levels (10), which persisted for 8 wk after GH discontinuation (12).…”
Section: Discussionmentioning
confidence: 99%
“…(mg/l) post-GH Delta maximal change in IGFI from baseline P-III-P (U/ml) placebo and baseline Peak P-III-P (U/ml) post-GH IGF1 concentrations in elite athletes (15,16). An Australian study of 699 males and 404 female elite athletes found no significant difference in IGF1 concentrations between African, Asian, Oceanian and Caucasian athletes.…”
Section: Peak Igf1mentioning
confidence: 99%
“…4 The GH-2000 detection method provides high sensitivity and specificity 4 and has been validated in an independent GH administration study. 5 In addition, ethnicity 6 and sporting injuries 7 do not affect the reliability of the test. A limitation of all anti-doping tests based on measurements made at a single point in time is that training intensity and volume vary considerably during the season, and these may affect the values on which these tests are based.…”
Section: Introductionmentioning
confidence: 99%